Thank You to Our 2019 Reviewers. Issue 5 (29th April 2020) - Clark, Martyn; Bahr, Jean; Bierkens, Marc F. P.; Hall, Jim; Kollet, Stefan; Luce, Charles H.; Lundquist, Jessica; Mackay, D. Scott; van Meerveld, Ilja; Sanchez‐Vila, Xavier; Troch, Peter A.; Wohl, Ellen
Abstract : The editors of Water Resources Research (WRR) express their appreciation to the reviewers of articles submitted to the journal in 2019. We are proud of the rigorous WRR review process, where reviewers habitually go out of their way to improve the caliber and impact of WRR papers. Of the 2, 640 reviewers listed below for the 2, 034 new papers and 1, 129 revised papers submitted to the journal, 398 people reviewed three or more papers. On behalf of the journal and the authors, we thank all reviewers for their service and dedication to the scientific community. We look forward to the exciting advances that will be published in WRR in 2020. Key Points: The editors thank the 2019 peer reviewers